Variation in maternal sensitivity and the development of memory biases in preschoolers - Rifkin-Graboi, Anne; Tsotsi, Stella; Syazwana, Nadhrah; Stephenson, Mary C.; Sim, Lit Wee; Lee, Kerry (Frontiers in Behavioral Neuroscience, 2023)
Introduction Links between maternal sensitivity, hippocampal development, and memory abilities suggests early life insensitive care may shape structures and schemas influencing future decisions and stress management, biasing children to negative information. While it is possible that this pattern of neurodevelopment may have adaptive consequences, for example, preventing children from encountering untoward experience with future adversity, it may also leave some children at risk for the development of internalizing problems. Methods Here, in a Two Wave Study, we examine whether insensitive care predicts sub sequentially assessed memory biases for threatening (but not happy) stimuli in preschoolers (n = 49), and if such relations cut across different forms of relational memory, i.e., memory for relations between two “items,” between an “item” and its spatial location, and an “item” and its temporal sequence. In a subset (n = 18) we also examine links between caregiving, memory, and hippocampal subregion volume. Results Results indicate no main or interactive influence of gender on relational memory. However, insensitive caregiving predicted the difference between Angry and Happy memory during the Item-Space condition (B = 2.451, se = 0.969, p = 0.014, 95% CI (0.572, 4.340)], as well as memory for Angry (but not Happy) items [B = −2.203, se = 0.551, p < 0.001, 95% CI (−3.264,−1.094)]. Memory for the difference between Angry and Happy stimuli in the Space condition associated with larger right hippocampal body volumes (Rho = 0.639, p = 0.004). No relations were observed with internalizing problems. Discussion Results are discussed with reference to developmental stage and in consideration of whether negative biases may serve as an intermediate factor linking early life insensitive care and later socioemotional problems including an increased incidence of internalizing disorders.